S‐Nitrosoglutathione Reductase Deficiency Causes Aberrant Placental S‐Nitrosylation and Preeclampsia - Shathiyah Kulandavelu; Raul A. Dulce; Christopher I. Murray; Michael A. Bellio; Julia Fritsch; Rosemeire Kanashiro‐Takeuchi; Himanshu Arora; Ellena Paulino; Daniel Soetkamp; Wayne Balkan; Jenny E. Van Eyk; Joshua M. Hare (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Preeclampsia, a leading cause of maternal and fetal mortality and morbidity, is characterized by an increase in S‐nitrosylated proteins and reactive oxygen species, suggesting a pathophysiologic role for dysregulation in nitrosylation and nitrosative stress. Methods and Results Here, we show that mice lacking S‐nitrosoglutathione reductase (GSNOR−⁄−), a denitrosylase regulating protein S‐nitrosylation, exhibit a preeclampsia phenotype, including hypertension, proteinuria, renal pathology, cardiac concentric hypertrophy, decreased placental vascularization, and fetal growth retardation. Reactive oxygen species, NO, and peroxynitrite levels are elevated. Importantly, mass spectrometry reveals elevated placental S‐nitrosylated amino acid residues in GSNOR−⁄− mice. Ascorbate reverses the phenotype except for fetal weight, reduces the difference in the S‐nitrosoproteome, and identifies a unique set of S‐nitrosylated proteins in GSNOR−⁄− mice. Importantly, human preeclamptic placentas exhibit decreased GSNOR activity and increased nitrosative stress. Conclusions Therefore, deficiency of GSNOR creates dysregulation of placental S‐nitrosylation and preeclampsia in mice, which can be rescued by ascorbate. Coupled with similar findings in human placentas, these findings offer valuable insights and therapeutic implications for preeclampsia.